The Influence of Occupational Safety and Health on Performance through Job Satisfaction of Employees in the Production Department of PT. Successful, Steady and Prosperous Dompu Regency - Muhammad Juwaidin; Sri Wahyulina; Djoko Suprayetno (Tinta Emas Institute, 2023)
Performance is the result of work in terms of quality and quantity achieved by an employee in carrying out their duties in accordance with their responsibilities. Performance can be seen from whether the work can be carried out according to the predetermined time schedule, and whether the work results have achieved the targets expected by the company. This research aims to examine occupational safety and health variables on performance through job satisfaction of PT production employees. Sukses Mantap Sejahtera Dompu Regency, the type of research used is associative causal. The analysis technique used is path analysis using SPSS version 24. In this research, a sampling technique using the census method was used, so that the respondents in this research were all production employees of PT. Success Mantap Sejahtera Dompu Regency, totaling 93 employees. The results of the analysis show that occupational safety and health have a positive and significant effect on job satisfaction. Job satisfaction has a positive and significant effect on performance. Occupational safety and health have a direct positive and significant effect on performance. And the research results show that the satisfaction variable has a significant effect and partially mediates the influence of occupational safety and health on performance indirectly.